Shadow armies: political representation and strategic reality in America’s proxy wars - Farrow, R (2018)
In the years following September 11, 2001, the United States has placed a renewed emphasis on indirect intervention in conflicts through “proxy” forces. Despite other ideological differences, this trend has largely accelerated through the Presidencies of George W. Bush, Barack Obama, and Donald Trump. In this approach to warfare, the United States utilizes foreign governments and fighting forces to effect American goals, while reducing its reliance on American troops. These relationships are, by their nature, indirect, and, this thesis shows, arise in situations in which the United States wishes to obfuscate the true nature of its engagement, often because of political and reputational concerns. Accordingly, statements justifying these relationships, both inside the American government and to the American public, often evince a meaningful gap between the representations in the statements and the reality of a relationship. These statements often include representations of friendship and trust, arguments that the relationship will spare American lives or expenditure, or outright lies about the activity of a proxy force.